Blogs and Forums as Communication and Learning Tools in a MOOC - Mak, Sui Fai John; Williams, Roy; Mackness, Jenny (Proceedings of the International Conference on Networked Learning, 2010)
This paper presents the findings of research carried out into the use of blogs and forums as communication and learning tools in Connectivism and Connective Knowledge (CCK08), a Massive Open Online Course (MOOC) that was run between September and December 2008. The course was unique in many ways: it included a small credit-bearing course within a network; it was completely open and very large, and it included a unique aggregated network of blogs, which was one of the reasons why an unusually large number of online interactions took place in blogs rather than just in forums. The research used a survey and email interviews to explore a number of themes identified in the postings in the course which included: the importance of conceptual connections, personal connections, personal autonomy, media affordances and approaches to learning. The research identified three distinct clusters of respondents, with the following preferred modes of interaction: (1) blogging, (2) using the forums, (3) using both blogging and forums. A number of other modes of interaction were also used by the respondents. Many respondents used both blogs and forums for at least some of the time in the course. To a large extent, blogging and forum use correlated with specific individual learning styles and media affordances: the use of blogs was associated with the ability to create personal space for personal learning, quiet reflection and developing personal relationships with bloggers and others. The use of forums was associated with fast paced challenging interaction, relationships based on sharing of ideas, more open discussion and more links to the discussed themes and bigger picture. However, the research also identified three dimensions (home> <bazaar, long-loop> < short-loop, and engagement> < reflection) within which the new media provided different and new opportunities for participating in learning networks. Respondents used these to explore and develop their own affordances for learning in varied and even surprising and novel ways, sometimes using blogs or forums for particular purposes, but sometimes using them almost interchangeably. The research points to a maturing of media users in online learning. These users are developing their own personal learning networks, and using the new media in innovative and nuanced ways.